2013
DOI: 10.1016/j.bbamem.2013.04.026
|View full text |Cite
|
Sign up to set email alerts
|

Surface-enhanced infrared absorption spectroscopy (SEIRAS) to probe monolayers of membrane proteins

Abstract: Surface-enhanced infrared absorption spectroscopy (SEIRAS) represents a variation of conventional infrared spectroscopy and exploits the signal enhancement exerted by the plasmon resonance of nano-structured metal thin films. The surface enhancement decays in about 10nm with the distance from the surface and is, thus, perfectly suited to selectively probe monolayers of biomembranes. Peculiar to membrane proteins is their vectorial functionality, the probing of which requires proper orientation within the membr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
131
0
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(140 citation statements)
references
References 62 publications
(67 reference statements)
0
131
0
5
Order By: Relevance
“…In this context, ultrafast vibrational dynamics in membrane proteins, polymer films or at electrochemical interfaces can be envisioned which have up to now only been studied routinely with comparatively low temporal resolution (approximately nanoseconds). 21,33 In the context of low absorbing samples, possible signal enhancement effects gain significant attraction. In particular Au nanoparticles and roughened surfaces have been widely applied to obtain increased sensitivity in stationary as well as ultrafast spectroscopy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, ultrafast vibrational dynamics in membrane proteins, polymer films or at electrochemical interfaces can be envisioned which have up to now only been studied routinely with comparatively low temporal resolution (approximately nanoseconds). 21,33 In the context of low absorbing samples, possible signal enhancement effects gain significant attraction. In particular Au nanoparticles and roughened surfaces have been widely applied to obtain increased sensitivity in stationary as well as ultrafast spectroscopy.…”
Section: Discussionmentioning
confidence: 99%
“…ATR spectroscopy is usually based on odd orders of (non-)linear susceptibility (χ 1 , χ 3 , etc.) and has been widely used to obtain spectroscopic information from a variety of samples, including self-assembled organic monolayers (MLs) 20 , biological samples 21 or intermediates at electrochemical surfaces 22 . As such, ATR spectroscopy is a method that provides surface-sensitivity and comparatively high signal magnitudes along with a direct comparability between linear and nonlinear spectroscopic results.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Ataka and co-authors suggested a reduction of the SEIRA signal to 1/20 upon polarization variation [37]. In our experiment, the estimated reduction factor for the relative intensities of the corresponding TEIRA bands is 1/14.…”
Section: Resultsmentioning
confidence: 53%
“…As the wavelength of infrared radiation is much larger than the distance between metal nanoparticles, the surface optical properties of the metal are strongly dependent on the metal type, immobilized species, or surrounding medium [37]. Conversely, the polarizability of a metal particle is strongly associated with the nanoparticle shape and state of the polarization of the incident radiation [8].…”
Section: Introductionmentioning
confidence: 99%
“…In spectrum, the parallel dipole cannot be detected while the perpendicular dipole signal is enhanced. This is responsible for some abnormal IR enhancement of the adsorbed molecules in ATR-SEIRAS compared with non-adsorbed molecules, which is also useful to distinguish molecule orientation on metal surfaces [24].…”
Section: Enhancement Mechanismmentioning
confidence: 99%